Adsorption Isotherms of Methylene Blue in Aqueous Solution onto Activated Carbons Developed from Vine Shoots () by Physical and Chemical Methods - María Ruiz-Fernández; María Alexandre-Franco; Carmen Fernández-González; Vicente Gómez-Serrano (Adsorption Science & Technology)
Carbonaceous adsorbents (CAs) developed from vine shoots ( Vitis Vinifera , VS) and characterized texturally were used for the adsorption of Methylene Blue (MB) from aqueous solution. The CAs were prepared by physical activation in air, carbon dioxide and steam, and by chemical activation with H 3 PO 4 , ZnCl 2 and KOH. One commercial activated carbon (CAC) was also used. The CAs were analyzed texturally by gas adsorption, mercury porosimetry and density measurements. Physical activation yielded mainly macroporous CAs, whereas chemical activation gave rise to mainly mesoporous CAs with high micro- and macro-pore contents. CAC was an essentially microporous carbon. The affinity of MB towards the CAs was usually low, except for the carbon prepared by activation of VS with KOH at 800 °C for 2 h. This AC exhibited a better behaviour in the adsorption of MB than CAC. The development of macroporosity in the KOH activation product was considerable.